The Role of Mental Stress in Ischaemia with No Obstructive Coronary Artery Disease and Coronary Vasomotor Disorders - Roos ET van der Meer; Angela HEM Maas (European Cardiology Review)
Ischaemic heart disease has been estimated to affect 126.5 million people globally. Approximately 70% of patients with angina and suspected myocardial ischaemia show no signs of obstructed coronary arteries after coronary angiography, but may still demonstrate ischaemia. Ischaemia with no obstructive coronary artery disease (INOCA) is increasingly acknowledged as a serious condition because of its association with poor quality of life and elevated risk for cardiovascular events. The negative effects of psychological stress on INOCA are gaining more attention. Psychological stress is associated with adverse cardiovascular outcomes such as mental stress-induced myocardial ischaemia. Psychological stress includes anxiety, depression, anger and personality disturbances. Coronary microvascular dysfunction and coronary arterial spasm are phenotypes of coronary vasomotor disorders that are triggered by psychological distress and depression, thereby increasing cardiovascular disease risk. Coronary vasomotor disorders are often co-existent in INOCA patients and might be considered as a contributing factor to mental stress-associated adverse cardiovascular outcomes. Additionally, psychological stress induces endothelial dysfunction more often in (young) women with INOCA than in men. Overall, many studies demonstrate an association between mental stress, coronary microvascular dysfunction and coronary vasospasm in patients with INOCA – especially women. Future research on stress-reducing therapies that target coronary vasomotor disorders in patients with INOCA is needed. This is particularly the case in young adolescents, in whom this type of ischaemic heart disease is increasing.